EDUKASI KESEHATAN MENTAL MELALUI SUPPORT GROUP COMMUNICATION PADA MAYARAKAT DESA BANARAN KULON PROGO - Dian Juliarti Bantam; Egi Prawita; Wahyu Adi Mudiparwanto (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
This community service program aims to improve the mental health of residents of Banaran Village, Kulon Progo, through the Support Group Communication (SGC) approach. Mental health is an important aspect of improving the community's quality of life but is often overlooked, especially in rural areas. In addition, there is still social stigma and lack of access to mental health services that hinder people from obtaining psychological support. Therefore, the community service team provides a program for the formation and facilitation of support groups that involve villagers as active participants. This activity was carried out at the Banaran Village Hall which was attended by 20 PKK mothers. The activity lasted for 4 hours, starting from the opening session, providing materials, and closing. The Head of the Village opened this activity by providing direction to the PKK mothers and various to the community service team. Then the presentation of materials by the team included mental health education, counseling on support group communication, and the formation of support groups. Finally, the closing activity was carried out with a group photo and the presentation of souvenirs. Based on the results of the interview after the activity, it was found that with this education and support group, residents were able to overcome stress, anxiety, and other psychological problems more effectively, by involving support groups, in this case, the PKK mothers, thus creating a healthier, more productive and mutually supportive environment.